Anaemia among Students of Rural Chinas Elementary Schools: Prevalence and Correlates in Ningxia and Qinghais Poor Counties - Luo, Renfu; Zhang, Linxiu; Liu, Chengfang; Zhao, Qiran; Shi, Yaojiang; Miller, Grant; Yu, Elaine; Sharbono, Brian; Medina, Alexis; Rozelle, Scott; et al. (Journal of Health, Population and Nutrition, 2011)
Although the past few decades have seen rising incomes and increased government attention to rural development, many children in rural China still lack regular access to micronutrient-rich diets. Insufficient diets and poor knowledge of nutrition among the poor result in nutritional problems, including irondeficiency anaemia, which adversely affect attention and learning of students in school. Little research has been conducted in China documenting the prevalence of nutritional problems among vulnerable populations, such as school-age children, in rural areas. The absence of programmes to combat anaemia among students might be interpreted as a sign that the Government does not recognize its severity. The goals of this paper were to measure the prevalence of anaemia among school-age children in poor regions of Qinghai and Ningxia, to identify individual-, household- and school-based factors that correlate with anaemia in this region, and to report on the correlation between the anaemic status and the physical, psychological and cognitive outcomes. The results of a cross-sectional survey are reported here. The survey involved over 4,000 fourth and fifth grade students from 76 randomly-selected elementary schools in 10 poor counties in rural Qinghai province and Ningxia Hui Autonomous Region, located in the northwest region of China. Data were collected using a structured questionnaire and standardized tests. Trained professional nurses administered haemoglobin (Hb) tests (using Hemocue finger prick kits) and measured heights and weights of children. The baseline data showed that the overall anaemia rate was 24.9%, using the World Health Organization’s blood Hb cut-offs of 120 g/L for children aged 12 years and older and 115 g/L for children aged 11 years and under. Children who lived and ate at school had higher rates of anaemia, as did children whose parents worked in farms or were away from home. Children with parents who had lower levels of education were more likely to be anaemic. The anaemic status correlated with the adverse physical, cognitive and psychological outcomes among the students. Such findings are consistent with findings of other recent studies in poor, northwest areas of China and led to conclude that anaemia remains a serious health problem among children in parts of China. Keywords: Anaemia; Anaemia, Iron-deficiency; Cross-sectional studies; Educational performance; Primary school students; China DOI: http://dx.doi.org/10.3329/jhpn.v29i5.8901 JHPN 2011; 29(5): 471-485